Taste the state : South Carolina's signature foods, recipes & their stories - Mitchell, Kevin, 1970- (The University of South Carolina Press, 2021)
"South Carolina's singularly rich food tradition includes distinctive ingredients, such as the Bradford Watermelon, Sea Island White Flint Corn, Palmetto Asparagus, and Carolina Gold Rice, and signature dishes such as shrimp and grits, chicken bog, okra soup, Frogmore stew, and crab rice. Taste the State tells the stories of the most important of these ingredients and dishes in 82 engaging profiles. These portraits provide origin stories, the most classic recipes, tales of kitchen creativity and agricultural innovation, and Chef-Scholar Kevin Mitchell's distillation of traditions in several hallmark recipes. Taste the State explores the food of every part of South Carolina-the famous rice and seafood dishes of the Lowcountry; the Pee Dee's catfish and Pinebark stews; the smothered cabbage, pumpkin, and mustard-based barbecue of the Dutch Fork and Orangeburg; the red chicken stew of the midlands; the chestnuts, chinquapins, and corn bread recipes of mountain west. Contributions of Native peoples (hominy grits, squashes, beans), the Gullah-Geechee (field peas, okra, guinea squash, rice, sorghum), and European settlers (garden vegetables, grains, pigs, cattle) in the mixture of ingredients and techniques that would become Carolina cooking are carefully mapped. Intended for residents, visitors, and the curious, Taste the State presents the back stories of foods and dishes Native to or developed in South Carolina, cutting out the fakelore, tourist hype, and newly invented traditions. Here's true Carolina Cooking in all its cultural depth, historical vividness, and sumptuousness-the plain home cooking and the Charleston society banquets, the sweet potato pone and the Lady Baltimore Cake. With photographs and illustrations throughout"--